INVESTIGATING THE RELATIONSHIP BETWEEN ECONOMIC GROWTH AND HUMAN DEVELOPMENT INDEX: ARE THEY SIMULTANEOUSLY RELATED ? - Nababan, Tongam Sihol; Panjaitan, Raya; Panjaitan, Ferry; Napitupulu, Sungguli (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
This study aims to investigate and prove whether economic growth and the human development index, each of which is influenced by its determinants, have a simultaneous relationship. The data used is secondary data in the form of panel data from North Sumatra Province consisting of 29 districts / cities for the period 2018 - 2022. The analysis method used is simultaneous equation with two stages least square. The study results show that the variables that have a positive and significant effect on economic growth are the output value variable of large and medium industries and the labor force participation rate variable, while the employment opportunity variable has a negative and significant effect on economic growth. The variables that have a positive and significant effect on the human development index variable are the per capita income variable and the life expectancy variable. However, the economic growth variable has a negative and significant effect on the human development index. By using two stages least square analysis, it is found that economic growth does not have a simultaneous relationship with the human development index variable.